Quantification and definiteness/indefiniteness: integration and functional identity of semantic categories - Kiklewicz, Aleksander (Lingua Posnaniensis, 2017)
The reference theory popular in 1970-1990s, which aimed at integrating various forms of semantic determination of lexical units of the language analysed from the syntax perspective, provides the starting point for the author. Quantification and definiteness/indefiniteness were treated in numerous publications from that period as varieties of the same semantic category, i.e. determination of the referential status of nominal groups. The author assumes that both categories demonstrate functional independence, therefore their exponents form opposites. Consequently, the quantification model of definiteness/indefiniteness, cultivated by some researchers, is not supported in the language material, being rather a strictly logical structure. At the same time, the author demonstrates that certain relations and dependencies occur between the two categories. Four aspects of such dependencies: selection, implication, collocation and derivation, are examined in the paper using Polish language materials and materials of other European languages.